Proposal of Fiersiphontina gen. nov., redescription of Fiersiphontina sensillata comb. nov., and new data on the distribution of Spiniferaphonte (Copepoda, Harpacticoida, Laophontidae) - Bruno, Maria Cristina; Cottarelli, Vezio (Zootaxa, 2011)
The taxonomic position and original description of Laophontina sensillata Wells & Rao, 1987 are reviewed based on specimens collected from the interstitial fauna of littoral coral sands of several islands of the Philippines and New Caledonia, and the species is designated as the type species of Fiersiphontina gen. nov. The new genus is proposed based on the total loss of sexual dimorphism in the P3 and P4 exopods, and the sexual dimorphism in P2 exopod. Fiersiphontina is highly adapted to the littoral interstitial habitat of coral sandy beaches, and is related to Laophontina Norman & T. Scott, 1905, Wellsiphontina Fiers, 1991 and Spiniferaphonte Gheerardyn & Fiers, 2007. The shared characteristics that indicate a strong affinity of Fiersiphontina to Spiniferaphonte are the robust, dorsally bent, and strongly sclerotised caudal seta V and the morphology of the genital field. The phylogenetic relationship of Spiniferaphonte and Fiersiphontina is also suggested by the analysis of the last ontogenetic phases of the species of the two genera. We re-describe here the adults of both sexes, describe the last three copepodid stages of Fiersiphontina sensillata (Wells & Rao, 1987) comb. nov., and provide notes on the biogeography of the four related genera, and on the ecology of Fiersiphontina and Spiniferaphonte.